2019
DOI: 10.2172/1511048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Versatile Experimental Salt Irradiation Loop (VESIL) inside the Advanced Test Reactor

Abstract: A Versatile Experimental Salt Irradiation Loop (VESIL) is under investigation at Idaho National Laboratory. An initial feasibility study was conducted for potential deployment inside the Advanced Test Reactor (ATR). Historical salt-irradiation tests are reviewed and summarized in this report. The study also surveys available instrumentation for this type of application and identifies key design and testing requirements. Neutronic analysis was performed in different ATR position for various salt candidates usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Some studies have qualitatively suggested that SM-LWRs could achieve equal or lower specific capital costs (i.e., capital costs per unit of nameplate electrical generating capacity) compared to LM-LWRs [10,11]. However, quantitative meta-analyses and other quantitative studies have not supported these findings [6,12]. These quantitative studies concluded that while individual SM-LWRs are expected to have lower total capital costs per reactor or plant, their specific capital costs are likely to be significantly higher than those of LM-LWRs [6,13].…”
Section: Figure 1 Annual Capacity Additions From Commercial Nuclear P...mentioning
confidence: 99%
“…Some studies have qualitatively suggested that SM-LWRs could achieve equal or lower specific capital costs (i.e., capital costs per unit of nameplate electrical generating capacity) compared to LM-LWRs [10,11]. However, quantitative meta-analyses and other quantitative studies have not supported these findings [6,12]. These quantitative studies concluded that while individual SM-LWRs are expected to have lower total capital costs per reactor or plant, their specific capital costs are likely to be significantly higher than those of LM-LWRs [6,13].…”
Section: Figure 1 Annual Capacity Additions From Commercial Nuclear P...mentioning
confidence: 99%
“…To provide the capability for an integrated effects testing platform to study the mechanisms outlined above for MSRs, the Versatile Experimental Salt Irradiation Loop (VESIL) is currently under consideration at Idaho National Laboratory (INL) for deployment in the Advanced Test Reactor (ATR) [10]. A feasibility assessment of this capability is carried out in this research article.…”
Section: Ib Background On Vesilmentioning
confidence: 99%
“…A schematic illustration of the loop is shown in Figure 1. Natural circulation was opted for, following an INL internal review that concluded that the development needs for a pump capable of withstanding the high neutron flux in the ATR and the corrosive salt environment would be prohibitive [10]. Two wall boundaries provide additional barriers to release.…”
Section: Ib Background On Vesilmentioning
confidence: 99%
“…The Versatile Experimental Salt Irradiation Loop (VESIL) shown below in Figure 1a, is a proposed fuel-bearing integrated effect experiment currently under investigation at Idaho National Laboratory (INL) [1]. This natural circulation molten salt loop would contain a fuel-bearing salt and is envisaged to be irradiated in one of the I-positions of the Advanced Test Reactor (ATR).…”
Section: Introductionmentioning
confidence: 99%